THE EVOLUTION OF ZELIANGRONG NAGAS IN MANIPUR - Devi, Sapam Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Zeliangrong Nagas constitute a major portion of the indigenous tribes of Manipur. The term “Zeliangrong” is a composite name of the cognate tribes of Zeme, Liangmei, and Rongmei, which was coined on 15 February, 1947 at the first Zeliangrong Conference when the Zeliangrong Council was established at Imphal. The term is an acronym of the prefixes of the respective three tribes- ‘Ze’ from Zeme, ‘Liang’ from Laingmei and ‘Rong’ from Rongmei. The basis of the naming consists of the common ethnic, linguistic, social and cultural origin of the kindred tribes. The original homeland and the migration of Zeliangrong Nagas have not been fully studied. There are two views, one view suggesting that they might have migrated from foreign lands, and the other view insisting that they were all settled in places where they are now since the beginning of human being.